Design and evaluation of magnetic-targeted bilosomal gel for rheumatoid arthritis: flurbiprofen delivery using superparamagnetic iron oxide nanoparticles - Mushtaq, Rayan Y.; Naveen, Nimbagal Raghavendra; Rolla, Krishna Jayanth; Al Shmrany, Humood; Alshehri, Sameer; Salawi, Ahmad; Kurakula, Mallesh; Alghamdi, Majed A.; Rizg, Waleed Y.; Bakhaidar, Rana B.; Abualsunun, Walaa A.; Hosny, Khaled M.; et al. (Frontiers in Pharmacology, 2024)
The research systematically enhanced the fabrication process of flubiprofen-loaded bilosomes (FSB) through the application of Quality by Design (QbD) principles and Design of Experiments (DOE). This optimized formulation yielded particles measuring 453.60 nm in size with a remarkable entrapment efficiency of 91.57%. By integrating superparamagnetic iron oxide nanoparticles (SPIONs), the FSB gained magnetic responsiveness, thereby enhancing its potential for targeted drug delivery. Evaluations of morphology and in vitro release patterns affirmed the structural integrity and sustained release characteristics of the FSB formulation.Additionally, the formulation of an in situ forming hydrogel with FSB exhibited desirable numerical properties suitable for injectable applications, including a rapid gelation time of approximately 40 ± 1.8 seconds and controlled drug release kinetics. In vivo studies conducted on osteoarthritic rats provided numerical evidence of the efficacy of FSB-loaded hydrogel, demonstrating a substantial 27.83% reduction in joint inflammation and an impressive 85% improvement in locomotor activity. This comprehensive investigation, supported by numerical results, underscores the potential of FSB as a promising targeted drug delivery system for effective management of osteoarthritis.